2010
DOI: 10.1021/ic902281a
|View full text |Cite
|
Sign up to set email alerts
|

Cyclometalated Platinum(II) 6-Phenyl-4-(9,9-dihexylfluoren-2-yl)-2,2′-bipyridine Complexes: Synthesis, Photophysics, and Nonlinear Absorption

Abstract: A series of mononuclear and dinuclear cyclometalated platinum(II) 6-phenyl-4-(9,9-dihexylfluoren-2-yl)-2,2'-bipyridine complexes (F-1-F-5) were synthesized and their photophysical properties were systematically investigated. All complexes exhibit strong (1)pi,pi* absorption bands in the UV region, and a broad, structureless charge transfer band in the visible region. The charge-transfer band is broadened and red-shifted for F-3-F-5 compared to those for F-1 and F-2 because of the electron-donating acetylide li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
60
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 56 publications
7
60
0
Order By: Relevance
“…This causes the blue-shift of the UV-vis absorption spectrum. This phenomenon is also in accordance with that observed in many of the Pt(II) bipyridyl or terpyridyl complexes reported in the literatures [19,20].…”
Section: Chart 1 Structures Of Pt(ii) Complexes (1a-1f)supporting
confidence: 93%
See 3 more Smart Citations
“…This causes the blue-shift of the UV-vis absorption spectrum. This phenomenon is also in accordance with that observed in many of the Pt(II) bipyridyl or terpyridyl complexes reported in the literatures [19,20].…”
Section: Chart 1 Structures Of Pt(ii) Complexes (1a-1f)supporting
confidence: 93%
“…Meanwhile, 1a and 1b show more structured bands, which are indicative of an emitting state mixed with some intraligand 3 π,π* character. These assignments are also consistent with the literature report for similar complexes [19][20][21][22][23][24][25][26][27][28]. Furthermore, because 1a-1f all contain the same 4'-phenyl-2,2':6',2″-terpyridyl Pt(II) chloride component, the observed difference in emission should be attributed to the different natures of the substituents attached on the terminal phenyl unit, especially the electron-donating or electron-withdrawing ability of the substituents.…”
Section: Chart 1 Structures Of Pt(ii) Complexes (1a-1f)supporting
confidence: 91%
See 2 more Smart Citations
“…[1,2] Having the same shape and electronic configuration as 2,2′:6′,2′′-terpyridine (terpy), [3] the (Phbpy) -anion provides very stable tridentate binding and the cyclometalation, requiring C-H activation of the phenyl core, can be carried out at moderate conditions, usually by heating suitable Pt II or Pd II precursors and the C-H functionalised protoligands (ligand precursors, prior to metalation). [1,2,[4][5][6][7][8][9][10][11][12][13][14] Very soon after their initial use, it was found that many Pt II derivatives of the Phbpy ligand show intense luminescence, some even at ambient temperature. [11,[15][16][17][18][19] One reason lies in the destabilisation of dark metal-centred excited states associ-to 0.44 in PMMA matrices.…”
Section: Introductionmentioning
confidence: 99%